Soil pH and aridity influence distributions of branched tetraether lipids in grassland soils along an aridity transect - Jingjing Guo; Ma, Tian; Liu, Nana; Zhang, Xinying; Hu, Huifeng; Ma, Wenhong; Wang, Zhiheng; Feng, Xiaojuan; Peterse, Francien (Organic GeochemistryOrganic Geochemistry, 2022)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are membrane lipids of certain soil bacteria, and their relative distributions are used as a proxy for air temperature and soil pH. While temperature is recorded by the degree of methylation, soil pH is reflected by the amount of internal cyclization and the relative abundance of 6-methyl isomers. Since the exact producers of brGDGTs remain enigmatic, the mechanisms underlying their empirical relationships with temperature and soil pH, and thus the reliability of brGDGT-based paleorecords, are not well understood, especially in arid regions where mean annual precipitation (MAP) is less than 500 mm. Here, we evaluate the influence of soil pH and aridity on brGDGT distributions in grassland soils along an aridity transect (MAP = 173–415 mm) in Inner Mongolia. While the absolute and fractional abundance of 6-methyl brGDGTs increases with increasing soil pH and aridity, following the trend in the global surface soil calibration dataset, the degree of cyclization does not. This indicates that in arid regions, soil pH reconstructions based on the relative contribution of 6-methyl brGDGTs are likely more reliable than those based on the degree of cyclization. Furthermore, 5- and 6-methyl brGDGTs respond differently to aridity, supporting prior suggestions that the distribution of brGDGTs could be the result of changes in bacterial community composition instead of the direct physiological alteration of molecular structures by the source organisms. Analysis of the bacterial community composition in the same soil transect indicates that the relative abundance of Acidobacteria, the phylum hosting potential brGDGT source-organisms, shows a poor relationship with aridity. Instead, Verrucomicrobia (r2 = 0.70, p < 0.01), and its subclass Spartobacteria (r2 = 0.70, p < 0.01) in particular, show a significant negative correlation with aridity, resembling that of 5-methyl brGDGTs. Similarly, Actinobacteria are positively correlated with aridity (r2 = 0.59, p < 0.01), following the same trend as that of 6-methyl brGDGTs. The ability of certain cultures of Verrucomicrobia and Actinobacteria to produce iso-C15:0 fatty acids that could serve as building blocks for brGDGTs hints that Verrucomicrobia and Actinobacteria could possibly produce brGDGTs in arid soils.
Keywords: Acidobacteria; Actinobacteria; Aridity; brGDGTs; Environmental proxy; Soil pH; Verrucomicrobia